The Use of Vocabulary Based on Reading Text at the Second Year Students of MA Al Qodiri - Inayatul Mukarromah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
Various types of games in the teaching and learning process, especially in enriching English vocabulary related to reading texts, are the focus of this research. The author selected games suitable for the students' level and filtered six types of games to be applied in the classroom. Due to the students' lack of vocabulary related to derivatives, idioms, synonyms, and antonyms in reading texts, the researcher developed a learning strategy through vocabulary-based games using engaging, enjoyable, and challenging reading texts to enhance the vocabulary of second-year students at MA Al Qodiri Jember. The research design employed Classroom Action Research (CAR) with cyclical stages including planning, implementation, observation, and reflection, as well as quantitative data analysis. Berbagai jenis permainan dalam proses belajar mengajar di kelas, khususnya dalam memperkaya kosakata bahasa Inggris yang berkaitan dengan teks bacaan, menjadi fokus penelitian ini. Penulis memilih jenis-jenis permainan yang sesuai dengan tingkatan siswa dan menyaring enam jenis permainan untuk diterapkan di kelas. Karena kurangnya kosakata siswa yang berkaitan dengan derivatif, idiom, sinonim, dan antonim pada teks bacaan, peneliti mengembangkan strategi belajar melalui permainan berbasis kosakata melalui teks bacaan yang menarik, menyenangkan, dan menantang untuk meningkatkan kosakata siswa di kelas dua MA Al Qodiri Jember. Rancangan penelitian menggunakan Penelitian Tindakan Kelas (PTK) dengan tahapan siklus yang meliputi perencanaan, implementasi, observasi, dan refleksi, serta analisis data menggunakan pendekatan kuantitatif.